2020
DOI: 10.48550/arxiv.2008.04729
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AtrialJSQnet: A New Framework for Joint Segmentation and Quantification of Left Atrium and Scars Incorporating Spatial and Shape Information

Abstract: Left atrial (LA) and atrial scar segmentation from late gadolinium enhanced magnetic resonance imaging (LGE MRI) is an important task in clinical practice. The automatic segmentation is however still challenging, due to the poor image quality, the various LA shapes, the thin wall, and the surrounding enhanced regions. Previous methods normally solved the two tasks independently and ignored the intrinsic spatial relationship between LA and scars. In this work, we develop a new framework, namely AtrialJSQnet, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…In the DL-based approaches, both Chen et al (2018b) and Li et al (2020c) performed simultaneous LA and scar segmentation via multi-task learning. The simultaneous optimization scheme showed better performance than solving the two tasks independently, which ignored the intrinsic spatial relationship between LA and scars.…”
Section: La Cavity Segmentationmentioning
confidence: 99%
See 3 more Smart Citations
“…In the DL-based approaches, both Chen et al (2018b) and Li et al (2020c) performed simultaneous LA and scar segmentation via multi-task learning. The simultaneous optimization scheme showed better performance than solving the two tasks independently, which ignored the intrinsic spatial relationship between LA and scars.…”
Section: La Cavity Segmentationmentioning
confidence: 99%
“…The simultaneous optimization scheme showed better performance than solving the two tasks independently, which ignored the intrinsic spatial relationship between LA and scars. Besides, Li et al (2020c) introduced a spatial encoding (SE) loss to incorporate continuous spatial information of the LA. Their experiments showed that the SE loss could be effective to remove noisy patches in the final predicted segmentation, and therefore evidently reduced the Hausdorff distance (HD) value.…”
Section: La Cavity Segmentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, recognizing the orientation of different modality CMR images and adjusting them into standard format could be as challenging as the further computing tasks. Different from other work that focuses on segmentation or classification individually [10] or combine image segmentation with quantification [6] this work proposes a DNN-based framework to solve the cardiac image segmentation and orientation recognition tasks simultaneously.…”
Section: Introductionmentioning
confidence: 99%